Design, Synthesis and Characterization of Novel Arylamides Containing 1,2,4-triazole Nuclei for Possible Antimicrobial Activity - S. R. Dhol; P. M. Gami; R. C. Khunt; A. R. Parikh (E-Journal of Chemistry)
Diphenyl aceto hydrazide on reaction with carbon disulfide and potassium hydroxide gave potassium α,α-diphenyl acetamido dithiocarbamate, which on cyclisation with hydrazine hydrate yielded key intermediate 3-mercapto-4,N-amino-5-benzhydryl-1,2,4-triazoles. The key intermediate on condensation with different acid chloride afforded our titled compounds. The synthesised compounds have been confirmed elemental analyses and further supported by spectral data. All the synthesised compounds have been evaluated for their in vitroin vitro antimicrobial activity.